Analysis of Timeliness and Price on Customer Satisfaction Goride Electric - Purbanuara Parlindungan; Tedy Herdian; Mochammad Affan El Hanif; Miftah Hafid Adhitama (Jurnal Siber Multi Disiplin, 2026)
This study analyzes the impact of timeliness and price on customer satisfaction in the context of Gojek's innovative service, Goride Electric. This research uses quantitative methods with research instruments in the form of questionnaires. Data analysis was performed using SmartPLS version 4.0. Based on the results of this study, it shows that timeliness and pricing have a positive and significant impact on customer satisfaction, thereby increasing Gojek's competitive advantage in the online transportation service market. This research contributes to a better understanding of the dynamics of customer satisfaction in the context of innovative electric vehicle-based vehicle booking services, so that it can help Gojek improve its services and maintain customer loyalty.